Inovasi Digital dalam Audit : Implementasi Teknologi Blockchain untuk Transparansi dan Akurasi Laporan Keuangan - Muhammad Rizal; Yessica Amelia; Farah Qalbia (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This research examines the implementation of blockchain technology in enhancing transparency and accuracy of financial reports in the audit process. Using qualitative methods with comprehensive literature studies, this research analyzes three main aspects: blockchain's potential to improve financial report transparency, its impact on audit accuracy, and implementation challenges. Research findings show that blockchain characteristics such as immutability, transparency, and decentralization provide a strong foundation for a more efficient and reliable audit system. This technology enables real-time data verification, audit process automation, and more effective fraud prevention. Although there are challenges, such as infrastructure investment needs and human resource competency development, blockchain's long-term benefits in improving audit quality make it a promising solution for digital transformation in auditing. This research provides important contributions to modern audit practices and can serve as a reference for financial institutions and regulators in developing adaptive frameworks to technological developments.